Closed-system manufacturing of therapeutic NK cells using automated cell enrichment and concentration processes enables scalable, robust and cost-effective solutions - Kok, Nina; Dekkers, Zoë; Loos, Anica; Bos, Thomas; van den Broek, Puck; Post, Inge; Niessen, Bertine; Spanholtz, Jan; Huppert, Volker; Raimo, Monica (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundCell therapy is a promising field with the potential to improve outcomes for cancer and autoimmune disease patients. However, its complex and resource-intensive manufacturing requires costly infrastructure. Current processes, adapted from academic research, involve open handlings, manual processing, and repurposed equipment from biologics applications, raising quality and safety risks while increasing manufacturing costs. Closed, automated manufacturing systems can overcome these limitations.MethodsAllogeneic therapeutic natural killer (NK) cells can be generated from umbilical cord blood (UCB)-derived CD34+ hematopoietic stem cells in a closed, semi-automated process. Here, the automated CliniMACS Prodigy® system has been evaluated for reliability and performance in two unit operations, the enrichment of CD34+ stem cells from cord blood and the final product harvest and concentration. In this study, we report the outcome of these two processes across N = 36 different manufacturing runs performed during process development and GMP manufacturing for clinical release.ResultsEfficiency of CD34+ stem cell enrichment was evaluated across cord blood units with low (<4.50E06 CD34+ cells/unit, N = 11), medium (4.50-7.00E06 CD34+ cells, N = 13) or high (>7.00E06 CD34+ cells, N = 12) content. Robust performance was observed in all groups, with average CD34+ cell recoveries of 68.18%, 68.46%, and 71.94%, respectively. Higher purity was achieved in the high group (69.73%), compared to low (57.48%) and medium (62.11%). Factors such as UCB age, total nucleated cell count, and platelet or red blood cell content had no significant impact. For the final harvest and concentration process, we analyzed batches with low (<2 L, N = 7), medium (2–5 L, N = 14) or high cell culture volume (>5 L, N = 8). Approximatively 20% cell loss was reported, with average yields of 74.59% for low, 82.69% for medium, and 83.74% for high volumes. NK cell purity was stable at over 80%, and B and T cell impurities content remained low or undetectable.DiscussionThis study presents an agile solution using a single piece of equipment during two steps of a complex NK cell manufacturing process. This approach ensures closed system safety, automation, high consistency, and cost-effectiveness, enabling the successful delivery of high-quality allogeneic NK cell therapies to patients.